1990
DOI: 10.1037/0022-3514.59.3.384
|View full text |Cite
|
Sign up to set email alerts
|

"Do I know you?": The role of significant others in general social perception.

Abstract: This research used an idiographic method to examine the proposition that significant others are mentally represented as well-organized person categories that can influence social perception even more than representations of nonsignificant others, stereotypes, or traits. Together, Studies 1 and 2 showed that significant-other representations are richer, more distinctive, and more cognitively accessible than the other categories. Study 3 replicated the accessibility data and gauged inferential power by indirectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
303
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(334 citation statements)
references
References 42 publications
30
303
1
Order By: Relevance
“…Andersen and Cole (1990) documented the cognitive side of transference experimentally by asking participants to describe significant others and then embedding descriptions from their responses in descriptions of fictional characters. When subsequently asked to describe the characters, participants mistakenly attributed traits to the characters that were part of their schemas of the significant other but were not originally included in the character's description.…”
Section: The Role Of Mental Representations Of the Self Others And mentioning
confidence: 99%
“…Andersen and Cole (1990) documented the cognitive side of transference experimentally by asking participants to describe significant others and then embedding descriptions from their responses in descriptions of fictional characters. When subsequently asked to describe the characters, participants mistakenly attributed traits to the characters that were part of their schemas of the significant other but were not originally included in the character's description.…”
Section: The Role Of Mental Representations Of the Self Others And mentioning
confidence: 99%
“…Research by Andersen and her colleagues (e.g., Andersen & Cole, 1990) and by Lewicki (1985) has shown that exemplar-based knowledge can affect inferences about newly encountered persons who resemble the known exemplars in some way.…”
Section: General Simulation Approachmentioning
confidence: 99%
“…In addition, closer relationships ordinarily involve more intimate interactions and exposure to privileged information about the other's thoughts and feelings, and thus to a better sense of the other's complexities and depth of personality (e.g., Andersen, Glassman, & Gold, 1998;Andersen & Ross, 1984). People's mental representations of close others therefore include more concrete, detailed features than do their representations of more distant others, and their judgments about close others become associated with retrieval of lower level information (e.g., Andersen & Cole, 1990;Andersen et al, 1998;Idson & Miscel, 2001;Prentice, 1990). In contrast, the limited knowledge of low-level features regarding socially distant others typically requires one to represent information about these individuals more abstractly and to rely on broad and central features in judgments related to their actions (e.g., Jones & Nisbett, 1972;Park & Rothbart, 1982).…”
mentioning
confidence: 99%